Effect of organic farming on root microbiota, seed production and pathogen resistance in winter wheat fields - Claire Ricono; Cendrine Mony; Audrey Alignier; Stéphanie Aviron; Colette Bertrand; Pierre‐Antoine Precigout; Corinne Robert; Ting‐Ting Wang; Philippe Vandenkoornhuyse (Plants, People, Planet)
Societal Impact Statement Agricultural intensification is a major driver of biodiversity decline in agrosystems. For instance, it has been shown that conventional farming leads to a decline in soil microbial diversity and triggers a strong selection process, altering the functioning of the whole ecosystem. The present study shows that organic farming increases diversity and affects composition of crop plant microbiota, mostly as a response to field management and soil characteristics. Furthermore, crop plant microbiota influences crop production and resistance to pathogens. Therefore, agricultural practices affect plant performance through microorganism‐mediated changes, which may be important pillars of future sustainable crop production. Summary Agricultural intensification threatens biodiversity, but the effects of intensification on microorganisms are still overlooked despite their role in ecosystem functioning. Microorganisms associated with plants provide many services that affect plant growth and health. Organic farming is expected to strongly affect species composition, richness, and their interactions. We analyzed the effect of the farming system on endophytic microbial assemblages associated with winter wheat plants and plant performance in the field. We collected environmental data through farmer interviews, soil analyses, and plant inventories and analyzed root microbiota at vegetative and flowering stages. Organic farming increased fungal and bacterial diversity associated to wheat plants and affected species composition in most phyla. This effect was mostly due to soil characteristics and field management and a little to plant diversity in the field. Microbial responses were more pronounced at the late developmental stage, likely as a result of accumulative effect of management actions during plant development. Seed production and resistance to pathogens were related to specific phyla that are important for seed production and/or wheat resistance to septoriose. This work advances our understanding of how agricultural practices affect plant performance through microorganism‐mediated changes and supports the use of microorganisms as pillars of sustainable crop production.